Exploring The Existence, Survival and Working Mechanism of Traditional Gold Mines in Banyuwangi Regency - Pramadita Tiara Wardani; Setiadi Setiadi (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
Mining activities carried out by the community of Sumberagung Village show contradictory conditions. On the one hand, mining is a major source of income for residents who have difficulty finding other jobs. This activity drives the village economy and provides economic opportunities for the local community. However, on the other hand, mining practices often face various complex problems. This study discusses the resilience and working mechanisms of traditional gold mining in Sumberagung Village. This study uses ethnographic studies and a qualitative approach, with in-depth interviews, participatory observation, and document studies that identify the factors that enable the sustainability of this mining. The results show that the existence of traditional gold mining is supported by strong social and economic networks, with this activity being the main source of livelihood for some of the community. Their working mechanisms operate through informal cooperation and profit-sharing systems, creating an independent economic ecosystem. The resilience of this mining is also supported by local knowledge (local wisdom) that has been passed down from generation to generation, especially in identifying mining locations and simple gold ore processing. Although traditional mining can support the economy, the lifestyle in remote mining locations, which is male-dominated and lacks the presence and interaction of women, triggers inappropriate behavior, including harassment.